Reading texts : reading, responding, writing - McCormick, Kathleen. (D.C. Heath, 1987)
This book is divided into three parts: Understanding the Reading Situation, incorporates the central insights of recent reader-cenntered and culturally focused criticism; Understanding the Writing Situation with the goals and strategies of process-oriented; and Reading, Responding, Writing...